g) 3 [4+ (6-2)] + [3²-(6-2)]- (7-5) =
3[4+4] + [ 32 - 4]-(4-5) 3 (+8) + 4-4-2=
3+ 8 + 9 -4-2 = + 14,
esta bien?? doy corona comprobare
ghuertas040:
no está mal
Respuestas
Respuesta dada por:
2
✨RESPUESTA✨
=27
EXPLICACIÓN PASO A PASO
3(4+(6−2))+[3²−(6−2)]−(7−5)
=3(4+4)+[3²−(6−2)]−(7−5)
=(3)(8)+[3²−(6−2)]−(7−5)
=24+[3²−(6−2)]−(7−5)
=24+9−(6−2)−(7−5)
=24+9−4−(7−5)
=24+5−(7−5)
=29−(7−5)
=29−2
=27
espero que te sirva suerte!!!!
Preguntas similares
hace 1 año
hace 1 año
hace 1 año
hace 4 años
hace 4 años
hace 7 años
hace 7 años